Analisis Financial Distress Perusahaan Subsektor Real Estate Dan Property Di BEI Tahun 2012-2021 - Rizka Ardila Angger Wijayanti; Efriyani Sumastuti; Rita Meiriyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the effect of a causal relationship from leverage ratios, liquidity, and firm size as independent variables to financial distress as the dependent variable in real estate and property companies. The research population used was 84 real estate and property companies listed on the Indonesia Stock Exchange (IDX) during the 10-year research period in 2012-2021. The research sample was taken using a purpose sampling technique with 32 selected samples being companies that met the sampling criteria. The analytical method used in this study is a quantitative research method through descriptive statistical testing, classical assumption testing, multiple linear regression testing, and hypothesis testing using IBM SPSS 25 software. The results found that (H1) leverage has a sixnificant negative effect on financial distress with six value 0.003 < 0.05; (H2) liquidity has no sixnificant effect on financial distress with a sig value of 0.576 > 0.05; (H3) company size has a significant negative effect on financial distress with a sig value of 0.002 <0.05.